2019
DOI: 10.1109/access.2019.2927516
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Analysis Framework of Time-Sensitive Networking Using Real-Time Calculus

Abstract: In the field of intelligent connected vehicles, as the rate of in-vehicle communication continues to increase, the importance of real-time and reliability requirements has been more prominent. The time-sensitive networking (TSN) task group is dedicated to the amendments for meeting the urgent needs in the industrial field. In the implementation of the TSN, time latency bounds of critical traffic, memory bounds of nodes and utilization of transmission resources are needed to evaluate the feasibility of the TSNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In [5], Zhao et al suggested to allow TT windows to overlap with each other which improved the overall solution space. In [6], Zhang et al used the analytical model in [5] to evaluate the preemption effect on the worst-case TT latency performance. Although the presented model in [5] and [6] has enhanced the solution space compared with full-isolated windows, the TT window overlapping was not optimized with the targeted latency deadlines.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In [5], Zhao et al suggested to allow TT windows to overlap with each other which improved the overall solution space. In [6], Zhang et al used the analytical model in [5] to evaluate the preemption effect on the worst-case TT latency performance. Although the presented model in [5] and [6] has enhanced the solution space compared with full-isolated windows, the TT window overlapping was not optimized with the targeted latency deadlines.…”
Section: Related Workmentioning
confidence: 99%
“…In [6], Zhang et al used the analytical model in [5] to evaluate the preemption effect on the worst-case TT latency performance. Although the presented model in [5] and [6] has enhanced the solution space compared with full-isolated windows, the TT window overlapping was not optimized with the targeted latency deadlines. Moreover, the algorithms were implemented with node-based design without considering the offset difference between the same priority windows in the adjoining nodes [5], [6], [34], [35].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Luxi Zhao et al [12] proposed a network calculus-based approach to determine the worst-case end-toend delays of audio/video bridging traffic with non-preemption and preemption. Peng Zhang et al [13] presented an analysis framework of TSN to analyse the worst-case latency through real-time calculus. Although the above two approaches can calculate the worst-case delay by arithmetic, they rely too much on parameters and cannot automatically calculate.…”
Section: Introductionmentioning
confidence: 99%